Y chromosome shredding in Anopheles gambiae: Insight into the cellular dynamics of a novel synthetic sex ratio distorter. - Matteo Vitale; Nace Kranjc; Jessica Leigh; Kyrous Kyrou; Thomas Courty; Louise Marston; Silvia Grilli; Andrea Crisanti; Federica Bernardini (PLoS Genetics)
Despite efforts to explore the genome of the malaria vector Anopheles gambiae, the Y chromosome of this species remains enigmatic. The large number of repetitive and heterochromatic DNA sequences makes the Y chromosome exceptionally difficult to fully assemble, hampering the progress of gene editing techniques and functional studies for this chromosome. In this study, we made use of a bioinformatic platform to identify Y-specific repetitive DNA sequences that served as a target site for a CRISPR/Cas9 system. The activity of Cas9 in the reproductive organs of males caused damage to Y-bearing sperm without affecting their fertility, leading to a strong female bias in the progeny. Cytological investigation allowed us to identify meiotic defects and investigate sperm selection in this new synthetic sex ratio distorter system. In addition, alternative promoters enable us to target the Y chromosome in specific tissues and developmental stages of male mosquitoes, enabling studies that shed light on the role of this chromosome in male gametogenesis. This work paves the way for further insight into the poorly characterised Y chromosome of Anopheles gambiae. Moreover, the sex distorter strain we have generated promises to be a valuable tool for the advancement of studies in the field of developmental biology, with the potential to support the progress of genetic strategies aimed at controlling malaria mosquitoes and other pest species.